Enhancing Cultural Literacy: Developing the Tombak Kiai Folklore Book for Elementary Students - Rizki Nurazmi Fadhilah Diyaurrahman; Alfi Laila; Bagus Amirul Mukmin; Baharudin Baharudin; Abu Dharin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Integrating local wisdom into educational materials is essential for fostering students' cultural literacy. This study investigates the validity and effectiveness of the Tombak Kiai Upas folk storytelling book in enhancing the cultural literacy of fifth-grade students. A Research and Development (RD) approach was employed, utilizing the ADDIE model comprising analysis, design, development, implementation, and evaluation stages. The study involved 156 fifth-grade students from four elementary schools in Pakel District. Data were collected through expert validations (material and media) and pre-test/post-test assessments conducted during both small- and large-scale trials. The validation phase demonstrated high feasibility, with material experts awarding a 97% score and media experts a 95% score, based on criteria such as content relevance, completeness, and practicality. Effectiveness testing utilized the N-gain formula, revealing an average improvement score of 0.6587 (categorized as medium), alongside a 30-point increase from pre-test to post-test results. These findings confirm that the Tombak Kiai Upas storytelling book effectively enhances cultural literacy among fifth-grade students. The integration of local cultural elements within the narrative supports engagement and deeper understanding, aligning with current educational strategies focused on cultural competency.The Tombak Kiai Upas folk storytelling book is both valid and effective as a learning medium, highlighting the value of local wisdom-based educational resources in promoting cultural literacy at the elementary level.